The Evolving Role of Selenium in the Treatment of Graves' Disease and Ophthalmopathy. (19th January 2012) - Duntas, Leonidas H.
Abstract : Graves' disease (GD) and ophthalmopathy (GO) are organ-specific autoimmune-inflammatory disorders characterized by a complex pathogenesis. The inflammatory process is dominated by an imbalance of the antioxidant-oxidant mechanism, increased production of radical oxygen species (ROS), and cytokines which sustain the autoimmune process and perpetuate the disease. Recently, selenium, which is a powerful antioxidant, has been successfully applied in patients with mild GO, slowing the progression of disease, decreasing the clinical activity score, and appreciably improving the quality of life. The mechanisms of selenium action are variable. The aim of this review is to summarize the actions of selenium in GD and GO. Selenium as selenocysteine is incorporated in selenoproteins, such as glutathione peroxidase which catalyzes the degradation of hydrogen peroxide and lipid hydroperoxide that are increasingly produced in hyperthyroidism. Moreover, selenium decreases the formation of proinflammatory cytokines, while it contributes, in synergy with antithyroid drugs, to stabilization of the autoimmune process in GD and alleviation of GO. It is now to be clarified whether enforced nutritional supplementation has the same results and whether prolonging selenium administration may have an impact on the prevention of disease.